Social incentives as nudges for agricultural knowledge diffusion and willingness to pay for certified seeds: Experimental evidence from Uganda - Okello, J.J.; Shikuku, Kelvin Mashisia; Lagerkvist, Carl Johan; Rommel, J.; Jogo, W.; Ojwang, S.O.; Namanda, S.; Elungat, J. (Elsevier, 2023)
A transition from low-input subsistence farming in Sub-Saharan Africa will require the use of yield-increasing agricultural technologies. However, in developing countries, most farmers continue to rely heavily on pestinfested and disease-infected recycled seed from own or local sources leading to low yields. This study used a field experiment to examine the effect of a social incentive combined with goal setting on the diffusion of agricultural knowledge and uptake of quality certified seed by farmers. We relaxed the seed access and information/knowledge constraints by introducing improved varieties of sweetpotato in the study villages and providing training to carefully selected progressive farmers who were then linked to co-villagers. We find that social incentives combined with goal setting reduced the likelihood of the trained progressive farmers reaching out to co-villagers to share information and discuss farming. Further, social incentive combined with goal setting had no significant effect on knowledge and experimentation by progressive farmers, and on willingness to pay for improved seed – as elicited through auctions, our proxy for experimentation, by co-villagers. These findings suggest that the combination of goal setting and public recognition acted to crowd-out diffusion effort. We conclude that social incentive combined with goal setting by established progressive farmers already enjoying a certain degree of public recognition is not sufficient to induce effort in learning and experimentation with agricultural innovations. These results have implications for design of policy and extension services to promote adoption of agricultural technologies with proven food and nutrition security benefits in developing countries.